Phillips curve in Canada: A tale of import tariff and global value chain - Devaguptapu, Adviti; Dash, Pradyumna (Review of Economic Analysis, 2023)
In this paper, we re-examine the Phillips curve for Canada from June 1976 to October 2022 in a time-varying manner. Our findings reveal that the impulse response of inflation to the changes in the unemployment rate gap has reduced over time till 2010 and strengthened thereafter. The response of inflation to the changes in the unemployment rate gap has increased in short and medium horizons after 2010. On further examination, we find that changes in both average import tariff and forward participation in the global value chain have reduced the inflation response to the changes in the unemployment rate gap.